Organizational rewards satisfaction and work performance of HR professionals: A study of a group human capital in Ez Bank, Malaysia - Wan Mohd Noor, Wan Shakizah; Majid, Ahmad Ridzwan; Mohd Isa, Mohd Faizal; Daud, Zulkiflee; Zainol, Zairani (2013)
Rewards always play a significant role in influencing company’s growth and employees’ retention. Employees in this new era are more interested on how the organization uses its resources.Organizational rewards are one of the key elements to reward high-performer and eventually resulting in better performance and high employee retention.Nevertheless employees’ perceptions toward rewards over its transparency, fairness and objectivity are always be the key over the satisfaction of the rewards itself. Hence this study examines the relationship between organizational rewards and work performance. The target group is HR Professionals in EZ Bank, Malaysia.The HR professionals were given questionnaire regarding the rewards practice in EZ Bank and respond to questions accordingly.128 HR professionals participated in this study. Regression analysis results showed weak relationship between two components of rewards tested against work performance.The others, pay satisfaction and salary administration showed no relationship at all, thus having weak linear correlation with work performance.